2013
DOI: 10.1371/journal.pntd.0002543
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Visceral Leishmaniasis among Residents and Migrants in Kafta-Humera, Ethiopia

Abstract: BackgroundVisceral leishmaniasis is a lethal parasitic disease transmitted by phlebotomine sand flies. The largest focus of VL in Ethiopia is located in the lowland region bordering Sudan, where the epidemiology is complicated by the presence of thousands of seasonal agricultural workers who live under precarious conditions.Methodology/Principal FindingsWe conducted two parallel case-control studies to identify factors associated with VL risk in residents and migrants. The studies were conducted from 2009 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 22 publications
9
92
2
9
Order By: Relevance
“…At the same time, using impregnated bed net was one of the most important means of control of the disease according to the report of [19] who indicated that 72% of respondents in his study explained that using bed net was the most important means of control of the disease. In addition, [15] also stated strong protective effects observation in those people using bed net.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…At the same time, using impregnated bed net was one of the most important means of control of the disease according to the report of [19] who indicated that 72% of respondents in his study explained that using bed net was the most important means of control of the disease. In addition, [15] also stated strong protective effects observation in those people using bed net.…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, [15] indicated that 3.3% children younger than 5 years, 19.2% of children 5-14 years, and 8.6% of adults 40 years or older were affected.…”
Section: Discussionmentioning
confidence: 96%
“…The use of insecticide-treated bed nets (ITNs) prevents VL and other vector-borne diseases. In Ethiopia, using bed nets was found to decrease the risk of VL [38]. The use of ITNs avoids human–vector contact and thereby decreases the chance to be infected and also decreases the likelihood that sandflies will feed on infected individuals.…”
Section: Future Needsmentioning
confidence: 99%
“…Only one out of 30e100 infected cases develop typical VL. Factors that predispose the development of typical VL include youth, malnutrition, poverty, immune deficiency, and high leishmanial load [99]. Progression time to VL is usually about 2e8 months from contact with the infectious agent, but longer periods are also reported; significantly shorter cases, up to two weeks after infection, have also been described in the literature [100].…”
Section: Visceral Leishmaniasismentioning
confidence: 99%